2006
DOI: 10.1124/mol.106.026419
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Activity-Dependent Sodium Channel Inhibition by the Antidepressants Fluoxetine and Desipramine

Abstract: The effect of monoamine uptake inhibitor-type antidepressants on sodium channels of hippocampal neurons was investigated. Members of the tricyclic group of antidepressants are known to modify multiple targets, including sodium channels, whereas selective serotonin-reuptake inhibitors (SSRIs) are regarded as highly selective compounds, and their effect on sodium channels was not investigated in detail. In this study, a representative member of each group was chosen: the tricyclic antidepressant desipramine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 37 publications
4
45
0
1
Order By: Relevance
“…However, our IC 50 of 4.7 mM is very similar with that published by Harmer et al (2011), who reported an IC 50 of 4.9 mM using IonWorks assays from hNa v 1.5-expressing Chinese hamster ovary (CHO) cells maintained at a holding potential of 290 mV. These results suggest that the holding potential of the cell is very important to the affinity of fluoxetine for the channel, as it has been also shown in rat hippocampi neurons (Lenkey et al, 2006), suggesting that the fluoxetine binds with higher affinity to inactivated than to resting channels.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…However, our IC 50 of 4.7 mM is very similar with that published by Harmer et al (2011), who reported an IC 50 of 4.9 mM using IonWorks assays from hNa v 1.5-expressing Chinese hamster ovary (CHO) cells maintained at a holding potential of 290 mV. These results suggest that the holding potential of the cell is very important to the affinity of fluoxetine for the channel, as it has been also shown in rat hippocampi neurons (Lenkey et al, 2006), suggesting that the fluoxetine binds with higher affinity to inactivated than to resting channels.…”
Section: Discussionsupporting
confidence: 78%
“…A major finding of our work was that fluoxetine shifts the steady-state inactivation curve by 6.7 mV toward more hyperpolarized values, indicating that it binds to the inactivated state of Na v 1.5, as is the case with neuronal Na 1 channels (Lenkey et al, 2006). In addition to a tonic block, fluoxetine decreased Na v 1.5 currents in a usedependent manner when pulsing at 2, 5, and 10 Hz.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…5). These differences might be attributed to a greater magnitude of effects on slow inactivation or due to differences in effects on recovery from inactivation (Lenkey et al, 2006). GS967 Effect Requires a Local Anesthetic Interaction Site.…”
Section: Gs967 Block Of Human Cardiac Sodium Channelsmentioning
confidence: 99%
“…While these non-specific effects have been suggested to be essential for producing the antidepressant response, the fact that we do not know the mechanism of therapeutic action of antidepressants makes it difficult to separate the beneficial from the detrimental effects of these non-specific interactions. With the reuptake blocker type of antidepressants (including TCAs and SRIs), there exists a 100-1,000 fold-magnitude of difference between the concentrations at which selective inhibition of monoamine reuptake and the therapeutic antidepressant effect occurs (Bolo et al, 2000;Torres et al, 2003;Lenkey et al, 2006). The high concentrations required for therapeutic efficacy result in a substantial loss of drug specificity.…”
Section: Side Effects Of Antidepressant Pharmacotherapy: Consequencesmentioning
confidence: 99%